2016
DOI: 10.4236/odem.2016.44010
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Attitude and Practices Related on Prevention of Mosquito Borne Diseases and Sanitation Conditions in a Salvadoran Urban Community

Abstract: Introduction: In El Salvador Mosquito Borne Diseases (MBDs) is a serious public health problem due to produce morbidity and mortality. They produce a high economic loss, which contributes to the collapse of the public health system. Over the years, the Salvadoran public health system has invested large amounts of resources to minimize the problem through campaigns against MBDs. Despite this, the population is still affected by diseases such as dengue, and more recently chikungunya and zika outbreaks. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
3
12
0
1
Order By: Relevance
“…Our result is in agreement with other studies suggesting low knowledge in tropical countries such as Laos [17], Indonesia [18], Malaysia [19], Nepal [20], India [21][22][23], Yemen [24] and Sri Lanka [25]. Nevertheless, one study conducted on Sint Eustatius island in the Eastern Caribbean and one study conducted in El Salvador showed a higher level of knowledge about MBDs [26,27]. These differences may reflect a higher knowledge level in some places but could also be due to methodological differences.…”
Section: Discussionsupporting
confidence: 92%
“…Our result is in agreement with other studies suggesting low knowledge in tropical countries such as Laos [17], Indonesia [18], Malaysia [19], Nepal [20], India [21][22][23], Yemen [24] and Sri Lanka [25]. Nevertheless, one study conducted on Sint Eustatius island in the Eastern Caribbean and one study conducted in El Salvador showed a higher level of knowledge about MBDs [26,27]. These differences may reflect a higher knowledge level in some places but could also be due to methodological differences.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have confirmed the assumption that knowledge of dengue favors the adoption of preventive measures that promote the reduction of breeding sites for A. aegypti 13 . Another study has stated that the greater the knowledge, the greater the willingness to participate in research on dengue 14 .…”
Section: Discussionmentioning
confidence: 88%
“…The virus also can transmit without a vector. Vertical transmission can occur in an infected pregnant lady to her child and during labor [20,21]. Unprotected sexual intercourse, including male to male also being one of the transmission method.…”
Section: Transmissionmentioning
confidence: 99%